Role of peripheral sensory neuron mu-opioid receptors in nociceptive, inflammatory, and neuropathic pain. Issue 11 (14th September 2020) - Barpujari, Awinita; Ford, Neil; He, Shao-Qiu; Huang, Qian; Gaveriaux-Ruff, Claire; Dong, Xinzhong; Guan, Yun; Raja, Srinivasa
Abstract : Background and objective: The role of peripheral mu-opioid receptors (MOPs) in chronic pain conditions is not well understood. Here, we used a combination of mouse genetics, behavioral assays, and pharmacologic interventions to investigate the contribution of primary afferent MOPs to nociceptive, inflammatory, and neuropathic pain, as well as to opioid analgesia. Methods: We generated conditional knockout mice in which MOPs were selectively deleted in primary sensory neurons. Inflammatory and neuropathic pain states were induced in mutant and control wild-type mice and their behavioral responses to noxious stimuli were compared. Gross motor function was also evaluated. Immunohistochemistry was used to assess MOP expression in the dorsal root ganglia, periaqueductal gray, and small intestine. The effects of MOP agonists DALDA (dermorphin [D-Arg2, Lys4] (1–4) amide) and morphine were evaluated in pain behavior assays, and their effects on neuronal physiology in the dorsal root ganglia were evaluated in whole-cell patch-clamp recordings. Results: Conditional MOP knockouts and control mice exhibited similar behavioral responses to acute nociceptive stimuli and developed similar inflammation-induced hypersensitivity. Unilateral nerve injury in animals lacking peripheral MOPs induced enhanced, bilateral mechanical allodynia. Subcutaneously administered DALDA was unable to decrease the hypersensitivity induced by inflammation and nerve injury in MOP knockout animals, and morphine's antinociceptive effects were significantly attenuated in the absence of peripheral MOPs. Conclusion: MOPs in primary sensory neurons contribute to the modulation of neuropathic pain behavior and opioid analgesia. Our observations highlight the clinical potential of peripherally acting opioid agonists in the management of inflammatory and neuropathic pain.